Effects of Grafting on Kenaf Fiber Reinforced Poly Vinyl Chloride/Ethylene Vinyl Acetate Blend Composites - Abu Bakar, Nurfatimah (2011)
Kenaf fiber is an environmentally friendly alternative which can be used as important reinforcing filler for thermoplastic composites. Kenaf also can be a good potential to make significant contribution. The main objective of this works is to investigate the possibility of producing new composites with methyl methacrylate (MMA) grafted kenaf as filler by using poly (vinyl chloride)/ethylene vinyl acetate as a polymer matrix. Graft copolymerization of methyl methacrylate (MMA) onto kenaf fiber has been carried out. Response surface methodology (RSM) based on centre composite design (CCD) was used to evaluate the effects of process variables (temperature, reaction time and amount of hydrogen peroxide) and their interaction towards the attainment of their optimum condition (grafting percentage). According to statistical analysis, the grafting reaction model proved to be highly significant with a very low probability value (<0.0001). The optimum condition (Pg = 51.85%) obtained at the temperature of 60oC, reaction time, 112 min and the amount of hydrogen peroxide is 7 mL. The presence of the functional group in the grafted polymers was characterized by fourier transform infrared (FTIR) spectroscopy. Scanning electron microscopy (SEM) also confirmed the presence of poly methyl methacrylate (PMMA) on the surface of kenaf fiber. Effect of kenaf fiber and kenaf-g-PMMA on mechanical properties of poly (vinyl chloride) (PVC)/ethylene vinyl acetate (EVA) blend were studied. The composites were prepared by blending using HAAKE Rheomixer Polydrive R600/610 at temperature and rotor speed of 150oC and 50 rpm. Effect of different fiber loading (0%, 10%, 15%, 20% and 30%) on their tensile strength, tensile modulus, flexural modulus, impact strength and hardness were determined. An increasing trend was observed in the tensile modulus, flexural modulus and hardness while a slight decrease was observed in tensile strength and impact strength was decreased. This observation indicates that grafting PMMA on the surface of kenaf fiber was improved the interfacial adhesion between the matrix and fiber. Differential Scanning Calorimetric (DSC) results show that the EVA crystallization behaviour is significantly influenced by the presence of kenaf fiber. The incorporation of grafted and ungrafted kenaf did not affect the thermal stability of the composites. Dynamic mechanical analysis (DMA) showed an increase in the storage modulus of the grafted composites.